2021
DOI: 10.21037/tp-20-225
|View full text |Cite
|
Sign up to set email alerts
|

Association between vaccinations and clinical manifestations in children with COVID-19

Abstract: Background: The infection rate of Coronavirus Disease 2019 in children was less than that in adults. However, the underlining reason is not well known.Methods: Children with COVID-19 were recruited from two Children's Hospitals in Wuhan and Shanghai in this case-control study. The associations of initial symptoms with age, vaccinations of Bacillus Calmette Guerin (BCG), and influenza and pathogens were determined by Chi-square t-test.Results: We evaluated 248 confirmed cases, and 56 suspected cases with COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Regarding COVID-19, it has been proposed that trained innate immunity or heterologous T-cell responses induced by BCG vaccination may reduce disease incidence, morbidity and severity (Curtis et al, 2020;Giamarellos-Bourboulis et al, 2020;Jirjees et al, 2020;Kubota et al, 2020;Levi et al, 2021;Mantovani & Netea, 2020;Marín-Hernández et al, 2021;Pana et al, 2021;Wickramasinghe et al, 2020). However, considering the limitations of ecological studies, analyses of the links between BCG vaccination and COVID-19 incidence and mortality have shown no correlation (Hensel et al, 2020;Liu et al, 2021;Ricco & Ranzieri, 2021), negative correlation (Goswami et al, 2021;Singh et al, 2020) or changes in correlation patterns as the pandemic progresses (Kubota et al, 2020). Other factors that have been proposed to affect SARS-CoV-2 infection and disease morbidity and mortality include ABO blood group (higher and lower susceptibility to infection in individuals with A and O blood groups, respectively) (Hodžić et al, 2020;Wu et al, 2020), age (older age associated with COVID-19 severity and mortality) (Ho et al, 2020), antibody levels against glycan Galα1-3Galβ1-(3)4GlcNAc-R (α-Gal) present in midgut microbiota (lower antibody levels associated with higher disease severity) (Urra et al, 2020) and sex (male patients appear to be at higher risk of mortality) (Ritter & Kararigas, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding COVID-19, it has been proposed that trained innate immunity or heterologous T-cell responses induced by BCG vaccination may reduce disease incidence, morbidity and severity (Curtis et al, 2020;Giamarellos-Bourboulis et al, 2020;Jirjees et al, 2020;Kubota et al, 2020;Levi et al, 2021;Mantovani & Netea, 2020;Marín-Hernández et al, 2021;Pana et al, 2021;Wickramasinghe et al, 2020). However, considering the limitations of ecological studies, analyses of the links between BCG vaccination and COVID-19 incidence and mortality have shown no correlation (Hensel et al, 2020;Liu et al, 2021;Ricco & Ranzieri, 2021), negative correlation (Goswami et al, 2021;Singh et al, 2020) or changes in correlation patterns as the pandemic progresses (Kubota et al, 2020). Other factors that have been proposed to affect SARS-CoV-2 infection and disease morbidity and mortality include ABO blood group (higher and lower susceptibility to infection in individuals with A and O blood groups, respectively) (Hodžić et al, 2020;Wu et al, 2020), age (older age associated with COVID-19 severity and mortality) (Ho et al, 2020), antibody levels against glycan Galα1-3Galβ1-(3)4GlcNAc-R (α-Gal) present in midgut microbiota (lower antibody levels associated with higher disease severity) (Urra et al, 2020) and sex (male patients appear to be at higher risk of mortality) (Ritter & Kararigas, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low vaccination rate of pregnant women and children in China, they are susceptible to the Delta variant. 10,11 Evidence also showed that COVID-19 infected pregnant women had a higher ICU admission rate than those without gestation. 12 Therefore, we formulated a detailed plan for providing healthcare to children and pregnant women in quarantine.…”
Section: Discussionmentioning
confidence: 99%
“…9 Pregnant women and children in China are presumably vulnerable to the Delta strain due to their low vaccination rate. 10,11 It was reported that the pregnant women have a significantly higher ICU admission rate if infected by the SARS-Cov-2. 12 Previous publications also indicated that pregnant women and children under quarantine had higher rates of depressive symptoms, anxiety, and other negative effects.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of asymptomatic cases vaccinated with BCG was not significantly higher than that without BCG vaccination (30.7% vs 46.2%, P = 0.203). Initial symptoms were not related to the immunized influenza vaccine ( P = 0.267) [ 31 ]. Seropositive young adults had about one-fifth the risk of subsequent infection compared with seronegative individuals.…”
Section: Early Research On the Symptoms And Spreading Of The Sars-cov-2 Among Children And Young Peoplementioning
confidence: 99%